2004
DOI: 10.1002/cbic.200300779
|View full text |Cite
|
Sign up to set email alerts
|

Classifying Enzymes from Selectivity Fingerprints

Abstract: Fingerprints of lipases and esterases have been recorded by using an array of chiral fluorogenic aliphatic esters of increasing chain length (C(4)-C(16)). Classification of the enzyme series was carried out with selectivity data by clustering and principal component analysis (PCA). Enzymes were classified on the basis of selectivity for chain length (C(4)-C(6) vs. C(10)-C(16)) and of middle-chain-length (C(8)-C(10)) reactivity. A minimum set of nine substrates was defined by cluster analysis of relative reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 20 publications
0
31
0
Order By: Relevance
“…Using a tailored set of substrates, it is even possible to distinguish between closely related enzymes. Thus, lipases and esterases were analysed functionally using an array of 16 chiral fluorogenic aliphatic esters with varying chain length (R)-3a-h and (S)-3a-h ( Figure 1) [51]. A dissimilarity analysis shows that the functional fingerprints obtained allow lipases and esterases to be classified according to their reactivity.…”
Section: Figurementioning
confidence: 99%
“…Using a tailored set of substrates, it is even possible to distinguish between closely related enzymes. Thus, lipases and esterases were analysed functionally using an array of 16 chiral fluorogenic aliphatic esters with varying chain length (R)-3a-h and (S)-3a-h ( Figure 1) [51]. A dissimilarity analysis shows that the functional fingerprints obtained allow lipases and esterases to be classified according to their reactivity.…”
Section: Figurementioning
confidence: 99%
“…Depending on its particular structure, the cleaved alcohol is then directly decarboxylated or fi rst oxidized with periodate and then subjected to BSAcatalyzed β -elimination in order to release the chromophore/fl uorophore [80 -82] . This methodology is also applicable to the screening and characterization of enantio selective enzymes [83] . Disadvantages are the need for synthesis of the specifi cally designed substrates and that only end -point measurements are possible rather than quantifi cation of enzyme kinetics.…”
Section: Hydrolase Assaysmentioning
confidence: 99%
“…An enzyme fi ngerprinting study involving eight enantiomeric pairs of analogs of 19 with various acyl chain length showed that lipases and esterases can be distinguished by their chain length selectivity [34] . The corresponding nitrophenyl and dinitrophenyl derivatives 22 and 23 display similar reactivities [35] .…”
Section: The Clips -O Substrates With Periodatementioning
confidence: 99%